Reading a Feminist Response on â€œThe Book of Knowledgeâ€ based on Gadamerâ€™s Philosophical Hermeneutics - Kodir, Faqihuddin Abdul (IAIN Surakarta, 2017)
The position of woman and knowledge in Islamic perspective has been an interesting issue in Islamic studies. One of the female Muslim scholars who focus her studies on feminism is Saâ€™diyya Shaikh. By exploring Gadamerâ€™s philosophical hermeneutics, this paper is aimed at explaining the basic concepts of theÂ philosophical hermeneutics of Saâ€™diyya Shaikhâ€™s â€œKnowledge, Women, and Gender in the Hadith: a Feminist Interpretationâ€ published in 2014. The work is focused on the interpretation responding to the selected texts of the Hadith in â€œThe Book of Knowledgeâ€, the collection of the prophetic traditions by Sahih al-Bukhari. It was found out that prejudice influences Shaikhâ€™s motivation in interpreting the text. However, as there are neither merely subjective nor objective aspects in the interpretation, Shaikh positions herself in the structures of self-understanding which reveal â€œthe truthâ€ for her within a horizon. Indeed, Shaikhâ€™s interpretation is dynamic. Thus, it can still be fixed and changed to invite new perspectivesÂ KeywordsFeminism, Hermeneutics, Interpretation